1986
DOI: 10.1557/jmr.1986.0237
|View full text |Cite
|
Sign up to set email alerts
|

The quasicrystalline transformation in the AlCr system

Abstract: Amorphous Al go Cr 20 films were made by coevaporation and by room temperature ion irradiation of the coevaporated films. The amorphous phase was transformed into the quasicrystalline state through two routes: thermal and ion beam assisted anneal. The intensity of the quasicrystalline electron diffraction pattern increases continuously within the annealing temperature range from 547° to 607 °C. The starting state of the films (as-deposited or ionirradiated codeposited) had no effect on the thermal transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Phase formation of a quasicrystalline phase in an Al-Cr alloy by ion irradiation of an amorphous film was reported by Lilienfeld et al (1986). The structure of the binary phase Al 45 Cr 7 (-Al 7 Cr) phase was determined by Cooper (1960) in the space group C2/m, with a = 25.196, b = 7.574, c = 10.949 Å , = 128 43 0 .…”
Section: Structure Descriptionmentioning
confidence: 98%
“…Phase formation of a quasicrystalline phase in an Al-Cr alloy by ion irradiation of an amorphous film was reported by Lilienfeld et al (1986). The structure of the binary phase Al 45 Cr 7 (-Al 7 Cr) phase was determined by Cooper (1960) in the space group C2/m, with a = 25.196, b = 7.574, c = 10.949 Å , = 128 43 0 .…”
Section: Structure Descriptionmentioning
confidence: 98%
“…However, an orthorhombic phase was prepared by in situ heating of the -Al 11 Cr 2 phase at 1072 K for 2 h (Cao & Kuo, 2008b). The -Al 11 Cr 2 phase and the related orthorhombic phase are crucial for understanding the formation and stability of the Al-Cr icosahedral quasi-data reports crystal firstly reported by Lilienfeld et al (1986) shortly after the discovery of quasicrystals in rapidly solidified Al-Mn alloys (Shechtman et al, 1984). Inoue et al (1987) found that single-phase icosahedral quasicrystals have formed in the vicinity of about 15.4 at.% Cr in rapidly quenched Al-Cr alloys, and the quasicrystal can be approximately formulated to have the composition Al 11 Cr 2 .…”
Section: Structure Descriptionmentioning
confidence: 99%
“…So far, at least 20 binary quasicrystal systems have been found. [1][2][3][4][5][6] However, almost all binary quasicrystals were produced by rapid solidification, and they were in a metastable state. 7 Only one decagonal quasicrystal obtained by slow solidification in an Al-Co alloy was found to be a stable binary decagonal quasicrystal up to now, 8 although many stable decagonal quasicrystals have been obtained by a slow solidification and directional growth method in Al-Cu-Co, 9 Al-Cu-Co-Ge, 10,11 and Al-Co-Ni ͑Ref.…”
mentioning
confidence: 99%